Clinical Advances in the Diagnosis and Treatment of Biliary Tract Diseases (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In recent years, there have been remarkable advances in the diagnosis and treatment of biliary tract diseases. Among them, the advanced endoscopic treatments and anti-tumor therapies for biliary tract cancer are outstanding. This reprint contains the latest research articles and review articles focusing on the diagnosis and treatment of biliary tract diseases using endoscopic retrograde cholangiopancreatography (ERCP) or endoscopic ultrasounds (EUSs) for biliary stricture, cholecystitis, cholangitis, ampullary tumors, and chemotherapy for biliary tract cancer.